Metabolism and biomass vertical distribution of zooplankton in the Bransfield Strait during the austral summer of 2000 - Yebra, Lidia; Hernández León, Santiago; Almeida, Carlos; Bécognée, Pierrick (Polar Research, 2009)
11 pages, 3 figures, 2 tables The vertical distribution (0–550 m) of zooplankton biomass, and indices of respiration (electron transfer system [ETS]) and structural growth (aminoacyltRNA synthetases activity [AARS]), were studied in waters off the Antarctic Peninsula during the austral summer of 2000. The dominant species were the copepod Metridia gerlachei and the euphausiid Euphausia superba. We observed a vertical krill/copepod substitution in the water column. The zooplankton biomass in the layer at a depth of 200–500 m was of the same magnitude as the biomass in the layer at a depth of 0–200 m, indicating that biomass in the mesopelagic zone is an important fraction of the total zooplankton in Antarctic waters. The metabolic rates of the zooplankton community were sustained by less than 0.5% of the primary production in the area, suggesting that microplankton or small copepods are the main food source. Neither food availability nor predation seemed to control mesozooplankton biomass. The wide time lag between the abundance peak of the dominant copepod (M. gerlachei) and the phytoplankton bloom is suggested to be the main explanation for the low summer zooplankton biomass observed in these waters We thank the crew of the RV BIO Hespérides, the technicians of the Unidad de Tecnología Marina (CSIC) and the participants of the ESEPAC 2000 cruise for their support at sea, especially S. Agustí for inviting us to participate in the ESEPAC project (ANT97-0273). We are indebted to N. Agawin for kindly supplying primary production values obtained during the cruise, and X. Morán and I.A. Catalán for providing additional data. This work was undertaken while L. Yebra was at the Biological Oceanography Laboratory of the Universidad de Las Palmas de Gran Canaria, supported by grants from the Spanish Science and Education Ministry (MAR97-1036) and the University of Las Palmas de Gran Canaria. Completion of this work was funded by the European Social Fund (I3P programme, CSIC) Peer reviewed